25 ideas for simplifying EU law - UK. Department for Business, Enterprise & Regulatory Reform (London, 2008)
"Good regulation provides essential protection against risks in society for citizens, consumers, workers and business. The UK believes this is true for legislation agreed at EU level, just as much as it is for domestic legislation. However, if the European Union is to maintain its competitive advantage in the global market, it is also necessary at both the EU and domestic level to look for every opportunity to simplify legislation. Reducing administrative burdens, while ensuring that necessary protection is provided in the most proportionate way, is part of this drive for greater competitiveness. Cutting the time a company needs to spend on filling in forms, for example, can free up resources which can be used instead to raise productivity or create business growth. In many cases, burden reductions will also lead to savings for consumers as companies pass on the benefits to their customers. (…)"